Transferability of human capital and job switches - Hannu Piekkola (The Research Institute of the Finnish Economy (ETLA), 2002)
This paper uses a job duration model based on linked employeremployee data over the period 1989-1998 with an emphasis on the job mobility of the highly educated. It is shown that the job mobility of all prime age workers is sensitive to pecuniary incentives. However, wages as a whole include offsetting elements. It is shown that compensations for transferable human capital raise and compensations for firm-specific human capital decrease job switches. It also appears that, in technology firms and for highly educated, firm-level payments, especially rent sharing, are most important in inhibiting unwanted job seeking. High firm-level wages tend to decrease job-to-job switches but also to increase withdrawals from the workforce. Job switches in all firms also show a positive relation to age. However, the 49-64 age group is in a considerably worse labour market position. – wages ; compensation policy ; unemployment ; worker mobility ; linked employer-employee data – – Tutkimus tarkastelee työsuhteiden kestoa duraatiomallilla käyttäen otosta yhdistetystä työnantaja- ja yritysaineistosta Suomesta vuosilta 1989-1996, jossa on painotettu erityisesti korkeasti koulutettuja. Tutkimuksen mukaan palkkaus vaikuttaa merkittävästi parhaassa työiässä olevien työpaikkojen vaihtoon. Kuitenkin palkkauksessa on vastakkaisia elementtejä. Koulutuksesta ja työkokemuksesta maksettavat korvaukset ovat positiivisessa suhteessa työpaikan vaihtoon, kun taas yrityskohtainen palkkaus vähentää liikkuvuutta. Tutkimuksen mukaan erityisesti tulospalkkaus vähentää työntekijöiden työpaikkaliikkuvuutta. Korkeat palkat yrityksessä mm. Tulospalkkauksen johdosta tosin myös lisäävät todennäköisyyttä työmarkkinoilta poistumiselle. Työpaikan vaihdon todennäköisyys ei vähene iän myötä. Poikkeuksen muodostavat kuitenkin ikääntyneet yli 49 vuotiaat, joiden työmarkkina-asema on huono.
Keywords: J21; J31; J50; C22; C41; 330; Arbeitsmobilität; Ökonomischer Anreiz; Lohn; Humankapital; Zeitreihenanalyse; Finnland